Konsep Bid’ah Dalam Tafsir Al-Qurthubi: (Telaah Atas Tafsir Surah al-Hadid Ayat 27) - Sandimula, Nur Shadiq; Otta, Yusno Abdullah; Djamalullail, Usman (Prodi Ilmu Al-Qur'an dan Tafsir, 2024)
The issue of Bid'ah is a discussion that has often been debated among Muslims since ancient times until today. This is because there is still a vagueness of the concept of Bid'ah itself, the vagueness causes confusion in its application, giving rise to disputes among Muslims. The Qur'an as the most important source of concepts in Islam has basically drawn the concept of Bid'ah, especially found in QS. Al-Hadid [57]: 27. Therefore, the purpose of this study is to explore the concept of Bid'ah contained in the Qur'an. This research begins by analysing the word 'bid'ah' based on its root word, then defining the terminology of Bid'ah according to the scholars as a reference concept, and finally examining the interpretations of the scholars on the verse that discusses the concept of Bid'ah. The results of this study indicate that the exploration of the concept of Bid'ah based on QS. al-Hadid [57]: 27 illustrates the classification of the concept of Bid'ah which refers to its meaning in language, therefore in this verse, the Bid'ah performed by the perpetrators of Rahbaniyyah is actually considered praiseworthy with the reward (ajr), while the censure (dzamm) refers to those who do not maintain the practice as it should be. In conclusion, the Qur'an recognises the existence of good Bid'ah, as long as it does not contradict the religious texts.